Isolation of Specific Clones from Nonarrayed BAC Libraries through Homologous Recombination. (13th October 2010) - Nefedov, Mikhail; Carbone, Lucia; Field, Matthew; Schein, Jacquie; de Jong, Pieter J.
Abstract : We have developed a new approach to screen bacterial artificial chromosome (BAC) libraries by recombination selection. To test this method, we constructed an orangutan BAC library using an E. coli strain (DY380) with temperature inducible homologous recombination (HR) capability. We amplified one library segment, induced HR at 42 ∘ C to make it recombination proficient, and prepared electrocompetent cells for transformation with a kanamycin cassette to target sequences in the orangutan genome through terminal recombineering homologies. Kanamycin-resistant colonies were tested for the presence of BACs containing the targeted genes by the use of a PCR-assay to confirm the presence of the kanamycin insertion. The results indicate that this is an effective approach for screening clones. The advantage of recombination screening is that it avoids the high costs associated with the preparation, screening, and archival storage of arrayed BAC libraries. In addition, the screening can be conceivably combined with genetic engineering to create knockout and reporter constructs for functional studies.